A Co-Simulation Model Integrating a Musculoskeletal Human Model with Exoskeleton and Power Tool Model - Molz, Carla; Scherb, David; Löffelmann, Christopher; Sänger, Johannes; Yao, Zhejun; Lindenmann, Andreas; Matthiesen, Sven; Weidner, Robert; Wartzack, Sandro; Miehling, Jörg (Applied Sciences, 2024)
Working at and above head height with a power tool represents a common activity in craft and assembly applications. To assist and protect the user from overload and injuries in these situations, the development and use of application-specific support systems, such as exoskeletons and power tools, have greatly increased in recent years. Thus, the integration of aspects of the user-centered product development of support systems in the early phases of product development process has high potentials. A common approach to integrate the user early in the product development process is the use of musculoskeletal human models, which allow the evaluation of effects on the human body. This could also be applicable in the mentioned use case to enable the evaluation of the interactions for the user. Therefore, a co-simulation model for virtual modelling and simulating human–machine interactions is presented. The co-simulation model is made up of a musculoskeletal human model and the models of the technical systems (exoskeleton and power tool). By applying the co-simulation model, the impact of technical systems on the human body can be taken into account to derive design alternatives for the technical system due to the requirements of the user. The paper describes the design of the co-simulation model and particularly, the interaction of the submodels. The evaluation of the co-simulation model is carried out with the help of a subject study for the selected use case working at and above head height. The results show plausible results for the muscle loads considering the support by an exoskeleton. Furthermore, the comparison of simulated results to measured muscle activations via surface electromyography shows a good agreement. Thus, the co-simulation model passes the test for functionality and seems to be applicable for the derivation of design alternatives of technical systems regarding the user needs. In future, the co-simulation model will be further validated with a higher number of subjects and to implement design alterations in the technical systems.<br
Keywords: human–machine interaction; biomechanics; support systems; exoskeleton; product development; user-centered design; musculoskeletal human model

A Musculoskeletal Human Model-Based Approach for Evaluating Support Concepts of Exoskeletons for Selected Use Cases - Molz, Carla; Yao, Zhejun; Sänger, Johannes; Gwosch, Thomas; Weidner, Robert; Matthiesen, Sven; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2022)
This paper presents an approach for evaluating exoskeleton support concepts through biomechanical analyses on a musculoskeletal human model. By simplifying the support forces of an exoskeleton as external forces, different support concepts can be biomechanically evaluated for the respective use case without concrete design specifications of the exoskeleton. This enables an estimation of the resulting relief and strain on the human body in the early stages of exoskeleton development. To present the approach, the use case of working at and above head height with a power tool is chosen.
Keywords: user-centred design; design optimisation; supportive technologies; musculoskeletal human model; exoskeleton

A Novel Approach to Simulating Realistic Exoskeleton Behavior in Response to Human Motion - Yao, Zhejun; Seyed Milad Mir, Latifi; Molz, Carla; Scherb, David; Löffelmann, Christopher; Sänger, Johannes; Miehling, Jörg; Wartzack, Sandro; Lindenmann, Andreas; Matthiesen, Sven; Weidner, Robert (Robotics, 2024)
Simulation models are a valuable tool for exoskeleton development, especially for system optimization and evaluation. It allows an assessment of the performance and effectiveness of exoskeletons even at an early stage of their development without physical realization. Due to the closed physical interaction between the exoskeleton and the user, accurate modeling of the human–exoskeleton interaction in defined scenarios is essential for exoskeleton simulations. This paper presents a novel approach to simulate exoskeleton motion in response to human motion and the interaction forces at the physical interfaces between the human and the exoskeleton. Our approach uses a multibody model of a shoulder exoskeleton in MATLAB R2021b and imports human motion via virtual markers from a digital human model to simulate human–exoskeleton interaction. To validate the human-motion-based approach, simulated exoskeleton motion and interaction forces are compared with experimental data from a previous lab study. The results demonstrate the feasibility of our approach to simulate human–exoskeleton interaction based on human motion. In addition, the approach is used to optimize the support profile of an exoskeleton, indicating its potential to assist exoskeleton development prior to physical prototyping.<br
Keywords: exoskeleton model; exoskeleton simulation; human–exoskeleton interaction; evaluation; optimization; human motion

A posture prediction method for ergonomic assessment of user-product interactions while grasping using musculoskeletal human models - Hartmann, Carla; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
Using digital human models (DHMs) as the virtual representation of the human body enables the integration of ergonomic assessments in the product design process. Especially the use of DHMs in the early phases of product design can be decisive for competitive factors such as ergonomics or usability. Therefore, we present a method for automatic posture generation for grasping tasks using a musculoskeletal human model. This method enables ergonomic analyses without ergonomic knowledge of the product designer or subject tests. We implemented the presented method for a cylinder grasping scenario using the open source software OpenSim. Subsequently, we evaluated the implementation by means of a parameter stud
Keywords: Posture prediction; musculoskeletal simulation; digital human model

Co-Simulationsmodell zur nutzerzentrierten Entwicklung von Unterstützungssystemen: Am Beispiel von Tätigkeiten in und über Kopfhöhe mit einem Schulter-Exoskelett und einem Akkuschrauber - Yao, Zhejun; Molz, Carla; Sänger, Johannes; Miehling, Jörg; Germann, René; Wartzack, Sandro; Matthiesen, Sven; Weidner, Robert (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2021)
Unterstützungssysteme zeichnen sich durch eine erhöhte Mensch- Maschine-Interaktion aus. Diese Interaktion und ihre Auswirkungen haben große Bedeutung für die Entwicklung und Anwendung von Unterstützungssystemen und führen zu einer besonderen Herausforderung bei der Simulation entsprechender Systeme. Um diesen gerecht zu werden, wird ein Co-Simulationsmodell von Menschen, Exoskelett und Power-Tool entwickelt. Derartige Co-Simulationsmodelle ermöglichen bereits in der frühen Phase der Entwicklung der Unterstützungssysteme eine digitale Integration des Anwenders.<br
Keywords: Mensch-Maschine-Interaktion; Unterstützungssysteme; Produktentwicklung; Co-Simulation; Muskuloskelettales Menschmodell; Exoskelett und Power-Tool-Modelle; Biomechanik

Evaluation of Active Shoulder Exoskeleton Support to Deduce Application-Oriented Optimization Potentials for Overhead Work - Sänger, Johannes; Yao, Zhejun; Schubert, Tim; Wolf, Alexander; Molz, Carla; Miehling, Jörg; Wartzack, Sandro; Gwosch, Thomas; Matthiesen, Sven; Weidner, Robert (Applied Sciences, 2022)
Repetitive overhead work with a heavy load increases the risk for work-related shoulder disorders. Occupational exoskeletons supporting arm elevation are potential solutions to reduce that risk by lowering the physical strains on the shoulder. Many studies have reported a reduction in shoulder stress in various overhead tasks by using such exoskeletons. However, the support demand can vary in each phase of motion as well as in each individual task. This paper presents a laboratory study with five participants to evaluate the influence of the support level of an active shoulder exoskeleton in different motion phases (e.g., arm lifting, screw-in, and arm lowering of two overhead tasks) to identify the potential optimization of support at each phase. Results show that the support level of the exoskeleton should be adapted to the motion phase of the two chosen tasks. A higher support force is desired for the screw phase compared to the arm lifting and lowering phases, and the support level needs to be reduced immediately for arm lowering after the screw phase. The time for switching the support levels can be recognized by the electric current of the screwdrive
Keywords: human–machine interaction; biomechanical analysis; sEMG; interaction forces; user experience; power tool; exoskeleton

Method for Using IMU-Based Experimental Motion Data in BVH Format for Musculoskeletal Simulations via OpenSim - Wechsler, Iris; Wolf, Alexander; Fleischmann, Sophie; Waibel, Julian; Molz, Carla; Scherb, David; Shanbhag, Julian; Franz, Michael; Wartzack, Sandro; Miehling, Jörg (Sensors, 2023)
Biomechanical simulation allows for in silico estimations of biomechanical parameters such as muscle, joint and ligament forces. Experimental kinematic measurements are a prerequisite for musculoskeletal simulations using the inverse kinematics approach. Marker-based optical motion capture systems are frequently used to collect this motion data. As an alternative, IMU-based motion capture systems can be used. These systems allow flexible motion collection without nearly any restriction regarding the environment. However, one limitation with these systems is that there is no universal way to transfer IMU data from arbitrary full-body IMU measurement systems into musculoskeletal simulation software such as OpenSim. Thus, the objective of this study was to enable the transfer of collected motion data, stored as a BVH file, to OpenSim 4.4 to visualize and analyse the motion using musculoskeletal models. By using the concept of virtual markers, the motion saved in the BVH file is transferred to a musculoskeletal model. An experimental study with three participants was conducted to verify our method’s performance. Results show that the present method is capable of (1) transferring body dimensions saved in the BVH file to a generic musculoskeletal model and (2) correctly transferring the motion data saved in the BVH file to a musculoskeletal model in OpenSim 4.4.<br
Keywords: biomechanics; musculoskeletal modelling and simulation; inertial sensors; motion tracking; data transfer

Proactive Integration of User Data into Engineering Processes - A Generic Approach and Specific Examples - Wolf, Alexander; Buker, Tina; Molz, Carla; Scherb, David; Wartzack, Sandro; Miehling, Jörg (Human-Automation Interaction. Manufacturing, Services and User Experience, 2022)
User-centered design (UCD) describes an approach, which aims to increase customer satisfaction, comfort, usability, user experience, aesthetics and perceived quality by enhancing the fit between products and their users in the respective context of use. To achieve this goal, a multitude of different methods can be applied. All these methods integrate the user into the design process, in order to evaluate and improve the user-product interaction. This integration can be achieved via two different approaches. The classical approach on the one hand, integrates the user personally, e.g. focus groups, user tests, interviews or surveys. The proactive approach on the other hand, integrates the user in form of a user model, which is universally applicable for one aspect of user-product interaction, e.g. digital human models for the evaluation of physiological comfort and ergonomics or generic high-level guidelines for enhancing positive product emotions. The proactive approach is of great interest for industrial and engineering design, as it offers time- and cost-efficient user integration especially in the early, predominantly virtual phases of product design. This chapter takes a closer look at the proactive approach and presents four specific examples concerning computer aided ergonomics, assistive device design, preoperative evaluation of implants and product-related user stigma.
Keywords: User-centered design; User-product interaction; Proactive user integration